2015
DOI: 10.1371/journal.pone.0130974
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Interactions between the Members of the SMN-Gemins Complex in Drosophila

Abstract: The SMN-Gemins complex is composed of Gemins 2–8, Unrip and the survival motor neuron (SMN) protein. Limiting levels of SMN result in the neuromuscular disorder, spinal muscular atrophy (SMA), which is presently untreatable. The most-documented function of the SMN-Gemins complex concerns the assembly of spliceosomal small nuclear ribonucleoproteins (snRNPs). Despite multiple genetic studies, the Gemin proteins have not been identified as prominent modifiers of SMN-associated mutant phenotypes. In the present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…The SMN complex is central to cellular metabolism as demonstrated by its presence in nearly all eukaryotes [6]. In contrast to the expanded version in metazoans including humans, Drosophila was reported to have a minimal SMN complex composed of only SMN, Gem-in2/3/5, and, possibly, Unrip [11,[14][15][16]. Hence, it has been suggested that the human SMN complex gained complexity in evolution through the incorporation of the remaining Gemins [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SMN complex is central to cellular metabolism as demonstrated by its presence in nearly all eukaryotes [6]. In contrast to the expanded version in metazoans including humans, Drosophila was reported to have a minimal SMN complex composed of only SMN, Gem-in2/3/5, and, possibly, Unrip [11,[14][15][16]. Hence, it has been suggested that the human SMN complex gained complexity in evolution through the incorporation of the remaining Gemins [11].…”
Section: Discussionmentioning
confidence: 99%
“…Making use of this model, we and others have previously shown that loss of SMN, Gemin2, Gemin3, Gemin5, and Unrip leads to neuromuscular dysfunction . Importantly, components of the Drosophila SMN complex were shown to interact genetically in addition to physically . Attempting at furthering our understanding of the mechanics of the Drosophila SMN complex, here we report on the identification and initial characterisation of novel interacting partners.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…construct lacking its N-terminal helicase domain, called Gem3 BART(BORG et al 2015), were used in combination with a deficiency allele Df(1)ED6716 (RYDER et al 2007) that spans the 3F2-4B3 interval on the X chromosome that includes CG2941/Gaulos(LANFRANCO et al 2017). Loss of one copy of this region in combination with panmuscular expression of Gem3 BART led to a marked age-dependent enhancement of the phenotype(LANFRANCO et al 2017).…”
mentioning
confidence: 99%
“…Genetic interactions have been observed among SMN complex genes [23][24][25] . To study whether there is a synergy among the three genes involved in regeneration, we generated an smn1 and gemin5 double mutant and studied the effect of simultaneous depletion of two genes on morphology and hair cell regeneration.…”
Section: Divergent Roles For Smn Complex Members In Embryo Developmenmentioning
confidence: 99%